Influence of Resilience on Survival of Small and Medium Enterprises - Owenvbiugie, Robinson Osarumwense (International Business Education Journal, 2020)
The study assessed the influence of resilience skill for the survival of SMEs in Edo State. Two research questions guided the study, while research question two was hypothesized and tested. 236 respondents were used using a proportionate sampling technique from a population of 1117 business owners. This is 23.63% of the population. A descriptive survey was used. A reliability coefficient of 0.77 was obtained with the use of Cronbach alpha formula. Data were obtained with the aid of a questionnaire. The research question was answered with mean, while t-test for the hypothesis. From the result, it was discovered that resilience skill influences SMEs survival. The two groups of entrepreneurs used for the study did not show any significant difference in possession of resilience skill for SMEs survival. It was concluded that resilience skill is needed by entrepreneurs to a high extent. It was also concluded that males do not differ significantly from female entrepreneurs in possessing resilience skill for SMEs survival. Consequently, it was recommended that appraisal of SMEs operations should be on a consistent basis to check for lapses, make improvement and increase customers’ goodwill, among others.